Exploring the Power of Qur'anic Parenting to Build Family Resilience - Harahap, Aziddin; Harahap, Arman; Febriani, Budi; Pardamean, Muda; Syahputra Harahap, Hasmi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Parenting is the maximum effort of parents given to children to become individuals with noble character. Parenting patterns or parenting in Islam, is a complete unity that comes from the attitude of parents towards young children in how to care for, educate, guide, and foster children optimally based on the Qur'an and the Sunnah of the Prophet. The role of parents as a foundation in the household greatly influences the growth and development of children's attitudes, because the beginning of a child's life is in the hands of parents, this is as the Prophet said